Plasmolysis reveals novel p33 characteristics in N. benthamiana cells. - Vicken Aknadibossian (22676694) (2025)
A) GFP:p33-expressing cells at four dpi under plasmolysis revealed GFP:p33 localization to the Hechtian strands. B) Transiently expressed GFP:p33 localized within a vesicle budding from the plasma membrane under plasmolysis conditions in N. benthamiana epidermal cells at four dpi. C) GFP:p33-containing vesicles appeared to grow from punctate GFP:p33 deposits in the cell wall. The dashed boxed regions depict these vesicles. White arrows indicate the plasma membrane (PM), cell wall (CW), and Hechtian strands (H). C: cytoplasm.